Evaluasi Pengelolaan Sampah di Perusahaan Air Minum Dalam Kemasan - Mochamad Chaerul; Seranti Ninan Nury (Al-Ard: Jurnal Teknik Lingkungan, 2023)
Currently, bottled drinking water (AMDK) companies in Indonesia are growing rapidly due to the need for water that is ready for consumption by the community. This research aims to identify sources of waste and evaluate Solid Waste Management (SWM) system in a selected bottled water company. The research adopted descriptive analysis methods through field observations and compared existing SWM with best practices and available standards. In its production line, the selected AMDK company produces non-hazardous solid wastes from production and domestic activities. Non-hazarodus waste from production activity generated from rejected products in the bottled water production process, testing the quality of the bottled drinking water produced, product packaging, until product transportation for the distribution. Non-hazarodus waste from domestic activity/municipal solid waste (MSW) generated from employees and it contributed around 33.7% of the total non-hazardous waste generation. Â From the observation, the company have implemented MSW management by prioritizing the waste reduction and segregation at the source and at waste temporary storage (TPS), and waste processing such as composting and eco-brick innovations. Better campaign of waste segregation and sustainability of waste processing are some of recommendation resulted from the research to reduce as much as possible the amount of waste to be transported to the Final Processing Site (TPA).